Design of Energy Storage Circuits for Efficiency of Electric Power Usage in Computer Devices - Faisal Irsan Pasaribu; Partaonan Harahap; Muhammad Adam (Budapest International Research and Critics University, 2020)
The use of electricity with large capacity sometimes faces problems. These problems include a decrease in voltage that occurs in the channel. With the improvement of the quality of electric power on computer equipment at the Faculty of Engineering, University of Muhammadiyah, North Sumatra, it is expected to be able to improve the quality of electrical power. This improvement is expected to reduce the cost of electricity usage in the Faculty of Engineering, Muhammadiyah North Sumatra. To carry out improvements in the quality of electrical power, it is necessary to calculate the active power and apparent power. After doing these calculations, the determination of the capacitor value will be used. By carrying out these stages it is expected that the installation of Energy storage devices can improve the quality of electrical power. And by using energy storage devices will be clearly seen before and after the use of energy storage devices with the value of efficiency before and after namely: 87% (active power) and 91% (apparent power).